EFEKTIVITAS CAMPURAN SAMPAH KUBIS DAN DAUN MANGGA SEBAGAI KOMPOS DENGAN VARIASI AKTIVATOR - Kartika Damayanti; Mujiyono .; Handoyo . (GEMA LINGKUNGAN KESEHATAN, 2016)
Magetan society  rarely take advantage of the organic waste. So it is necessary to do research on composting. This study aims to determine the effectiveness of sewage treatmentusing cabbage and mango leaves as main material and activator used were cow dung, goatdung and EM4. This is a pre-experimental research. Data collected by the experiment, measured andobserved. 27 samples of 3 diferent-processes were 9 sample using cow manure activators, 9second sample using goat droppings activator and 9 third sample using activator EM4. Thedata were then analyzed by calculating the average weight reduction of waste.Analyses usingANOVA test. Based on the result of statistical test, it is known ρ sign 0,000 α (0,01) so that Hisaccepted or no difference to the effectiveness on variation activator mixture of cabbage andmango leaves as compost. The results showed that the use of cow dung activators weightdecreased 28.20%, temperature (27-37) ° C, pH (6.6 to 7), humidity (55-70)%. The use ofgoat dung activators weight down 40.90%, temperature (28-39) ° C, pH (6.7 to 7), humidity(65-75)%. The use of EM4 weight decreased 61%, temperature (27-40) ° C, pH (6.6 to 7),humidity (55-75)%. We recommend using EM4 activatorbecause the result is the best. Keep thetemperature and humidity so that the composting process is going well.